Model based analysis and identification of multiple fault parameters in coupled rotor systems with offset discs in the presence of angular misalignment and integrated with an active magnetic bearing. (23rd June 2019) - Srinivas, R.Siva; Tiwari, R.; Kannababu, Ch.
Abstract: In the present paper, the modelling, analysis and identification of various system faults in the presence of angular misalignment in coupled rotor-train systems integrated with an auxiliary AMB support has been presented. The method discussed in the paper quantifies the effect of misalignment by way of estimation of additive coupling stiffness (ACS). The novelty of the present paper lies in the modelling of a rotor-train-AMB system with two 4-dof simple rotors, each with an offset disc to have gyroscopic effects. With the combination of flexible coupling and weight dominance assumption the dynamic behaviour of rotor-bearing-coupling-AMB system has been characterized by the eight generalized coordinates of the two rotors. The coupling's angular stiffness has been modelled as the sum of direct stiffness and a time varying ACS, whose magnitude is affected by the amount of angular misalignment. A steering function has been selected such that the forced reponse due to coupling misalignment yields both odd and even harmonics in full spectrum. An identification algorithm based on least-squares regression technique in frequency domain has been developed using the forward and backward harmonics of rotor vibration and AMB current for the estimation of coupling direct stiffness, coupling additive stiffness, unbalance magnitude and its phase, equivalent viscous damping in each rotor, current and displacement constants of AMB. The assessment of severity of angular misalignment from the magnitude of estimated ACS is a novel deviation that has potential for practical application.